2007
DOI: 10.1007/s10194-007-0354-7
|View full text |Cite
|
Sign up to set email alerts
|

Sumatriptan 6 mg subcutaneous as an effective migraine treatment in patients with cutaneous allodynia who historically fail to respond to oral triptans

Abstract: The objective of the study was to assess the efficacy of 6 mg subcutaneous (SC) sumatriptan to treat migraine and the relationship between response of migraine and cutaneous allodynia in a population of migraine patients who historically failed to respond to oral triptan medications. This was an openlabel study consisting of patients with migraines who historically failed to respond to oral triptan medications. Forty-three patients were asked to treat three migraine attacks with 6 mg SC sumatriptan. The primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 15 publications
1
31
0
Order By: Relevance
“…Aura and attack duration, but not other migraine features, correlated with allodynia [16]. In a clinical trial studying nonresponders to triptans, both age and the number of years with migraine correlated with increasing numbers of allodynia symptoms [17].…”
Section: Allodynia In Episodic Migrainementioning
confidence: 99%
See 1 more Smart Citation
“…Aura and attack duration, but not other migraine features, correlated with allodynia [16]. In a clinical trial studying nonresponders to triptans, both age and the number of years with migraine correlated with increasing numbers of allodynia symptoms [17].…”
Section: Allodynia In Episodic Migrainementioning
confidence: 99%
“…Compared with migraine without allodynia, migraine with allodynia responds poorly to oral triptans[24, Class IV]. Studies of the response of migraine with allodynia to subcutaneous sumatriptan are contradictory: some studies suggest a poorer response than for nonallodynic migraine, but a larger study suggests similar pain-free rates for subjects with or without brush allodynia at 2 and 24 hours[17]. • Burstein et al[24, Class II] studied 34 migraine attacks for the ef-…”
mentioning
confidence: 98%
“…As sumatriptan has gained much attention as a potential therapeutic in many pain conditions (Bingham et al, 2001, Kanai et al, 2006, Diamond et al, 2007, Nikai et al, 2008) and has been shown to have both central and peripheral actions (Vera-Portocarrero et al, 2008), we also tested sumatriptan's role in TRPV1-evoked thermal hyperalgesia. Sumatriptan did not significantly attenuate TRPV1-evoked thermal hyperalgesia at 5 minutes, but did reverse hyperalgesia at 10 minutes, indicating that sumatriptan may be reducing the time course of TRPV1-evoked thermal hyperalgesia.…”
Section: Discussionmentioning
confidence: 99%
“…However, it will require a well‐controlled direct comparison (probably using a double‐dummy, double‐blind trial design) to determine whether this will translate into a therapeutic advantage. However, this will be a worthwhile hypothesis to test, given that it may also be true for s.c. sumatriptan 2,3,6 . Moreover, studies using metoclopramide to accelerate the absorption of aspirin provide a corollary 7 …”
Section: Discussionmentioning
confidence: 99%